2021
DOI: 10.3390/f12101408
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sucrose Supplementation on the Micropropagation of Salix viminalis L. Shoots in Semisolid Medium and Temporary Immersion Bioreactors

Abstract: The effect of sucrose concentration on the micropropagation of axillary shoots of willow was investigated. The following factors were examined: the culture system (semisolid medium in glass jars versus liquid medium in temporary immersion bioreactors), the type of explant (apical and basal sections), the frequency of immersion, and CO2 enrichment. Shoots and leaf growth were significantly higher in RITA® bioreactors than in the jars for all the sucrose treatments. Apical or basal sections of willow cultured in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 58 publications
1
21
0
Order By: Relevance
“…However, in our study with chestnut, we observed a positive correlation between sucrose supplementation and rooting. Similar responses have also been reported in other plants such as grapevine [ 50 ], kiwifruit [ 51 ], Chinese ash [ 52 ], poplar [ 53 ], and willow [ 40 ].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…However, in our study with chestnut, we observed a positive correlation between sucrose supplementation and rooting. Similar responses have also been reported in other plants such as grapevine [ 50 ], kiwifruit [ 51 ], Chinese ash [ 52 ], poplar [ 53 ], and willow [ 40 ].…”
Section: Discussionsupporting
confidence: 80%
“…These authors cultured chestnut shoots in tubes with a semisolid medium and without forced ventilation, and in these conditions shoot growth is frequently sucrose-dependent, as shown for kiwifruit ( Actinidia deliciosa ) [ 36 ], Arabidopsis [ 37 ], Pfaffia glomerata [ 38 ] and Vernonia condensata [ 39 ]. In a recent study we successfully micropropagated willow under high PPF and without sucrose when we used bioreactors ventilated with CO 2 -enriched air instead of jars without ventilation [ 40 ], and to obtain good proliferation in chestnut we applied the same principle, adding CO 2 -enriched air every 90 min to the bioreactors. Increased CO 2 concentration inside the flasks enabled shoot growth of other plants in media with low sucrose or without any supplementary carbohydrate, as reported for Paulownia fortunei (Seem.)…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that this feature promotes the photosynthetic ability of tissues, enabling the decrease or even the elimination of the conventional sugar supplementation [53,54]. For this reason, bioreactors have been used for the photoautotrophic propagation of several plants including eucalyptus [55][56][57][58], apple [59], poplar [60], bamboo [61] and willow [62], but to the best of our knowledge there are no reports of photoautotrophic protocols for plum or any other Prunus species. In the current study, we explored the feasibility of using commercial RITA© bioreactors for the propagation of plum photoautotrophically (without exogenous sugars) in an experimental unit which provided good results with willow [62].…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, bioreactors have been used for the photoautotrophic propagation of several plants including eucalyptus [55][56][57][58], apple [59], poplar [60], bamboo [61] and willow [62], but to the best of our knowledge there are no reports of photoautotrophic protocols for plum or any other Prunus species. In the current study, we explored the feasibility of using commercial RITA© bioreactors for the propagation of plum photoautotrophically (without exogenous sugars) in an experimental unit which provided good results with willow [62]. Previously, we carried out some experiments photomixotrophically (using 3% sucrose) to find the best growing conditions for the plum genotypes under study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation